Techno-nationalism and techno-globalism conflict and cooperation - Ostry, Sylvia A.; Nelson, Richard R. 1930- (Integrating national economies, 1995)
Techno-Nationalism and Techno-Globalism: Conflict and Cooperation is a broad-ranging study of the technological competitiveness of nations. It examines the origins of trade and public policy conflict in the United States, Japan, France, and Germany; the friction between countries caused by shifts in competitiveness; the role of trade policy in both causing and attempting to resolve these frictions; and the scope for new initiatives aimed at strengthening international cooperation. The authors argue that the margin of the U.S. technology lead has been narrowing since the 1960s, caused in part by the rise of Japanese industry in a variety of high-tech industries, and in part by the rapid circulation of information and diffusion of technology. They show how changes in technical competitiveness have created new sources of economic conflict between nations